SKIN TESTS: INDICATIONS AND CONTRAINDICATIONS - I. I. Balabolkin; D. Sh. Macharadze (Вопросы современной педиатрии, 2013)
The article contains modern views on indications and contraindications to skin tests as a part of allergological evaluation of patients. The literature review includes data, materials and conclusions of the international expert group, which have been recently developed. These data contribute to correct selection of such a wide-spread method of allergological evaluation, as skin tests.